ORIENTASI POLITIK PEMILIH MEMILIH NOMOR URUT 1 PADA PEMILIHAN UMUM ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) PROVINSI RIAU TAHUN 2014 (STUDI KASUS DAERAH PEMILIHAN RIAU II) - Wuwung Ahmadi; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Particulary in the list of elected candidates for the Regional Representatives Council (DPRD) of Riau Province in the general election in 2014 of people the winner of member Regional Representatives Council (DPRD) in numeric 1 is 39 people or 60%.. How Political Orientation Voters Choose Number 1 in the General Election of the Regional Representatives Council (DPRD) of Riau Province Year 2014 (Case Study of Electoral District of Riau II) ?. Purposes to know Political Orientation Voters Choose Number 1 in the General Election of the Regional Representatives Council (DPRD) of Riau Province Year 2014 (Case Study of Electoral District of Riau II). Research methods quantitative menthods. The research location in Kampar regency. Sampling probality sampling methods. Sources of primary data in the form of questionnaires and secondary data sources. Conclusion voter serial number 1 in the general election members of the Regional Representatives Council (DPRD) of Riau Province in 2014 are likely to see figures/candidate than the serial number of the figure/candidates. It can be seen from the results of the questionnaire as many as 50 respondents or 48,08% who agreed and 33 respondents or 31,73% that states could not agree in selecting candidates see figure/candidate, elector number 1 in the general election members of the Regional Representatives Council (DPRD) of Riau Province in 2014 either choose based on serial numbers and look at the figures /candidates have a tendency to political orientation positively are : based on common religion professed by candidates with voters (political orientation affective), based once candidates meeting/face to face with voters (political orientation affective), based on the program. Offered by candidatates during the campaign either a change in the social field as well as changes in the economic (political orientation evaluative).Keywords : Political Orientation, Selector, Choose, Serial Number, Electoral